2013
DOI: 10.1128/jvi.00021-13
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of Sequences in Pseudorabies Virus pUL34 That Are Required for Formation and Function of the Nuclear Egress Complex

Abstract: The nuclear egress complex (NEC) is required for efficient translocation of newly synthesized herpesvirus nucleocapsids from the nucleus to the cytosol. It consists of the type II membrane protein pUL34 which interacts with pUL31 at the inner nuclear membrane (INM). To map regions within pUL34 required for nuclear membrane targeting and pUL31 interaction, we constructed deletion/substitution mutations. Previously, we showed that 50 C-terminal amino acids (aa) of pseudorabies virus (PrV) pUL34, including the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 49 publications
3
35
0
Order By: Relevance
“…2 C and D) all decreased affinity by at least fivefold. This segment of UL50 and M50, particularly E56 and Y57, and the corresponding segment of their pseudorabies virus and Kaposi's sarcoma herpes virus homologs have previously been shown to be important for interaction with the other NEC subunit in less quantitative coimmunoprecipitation and colocalization assays (16,19,32,33). We also found that several substitutions that alter residues between positions 121 and 129 of M50 and 125 and 139 of UL50 (at the top of the groove and within the cavity in Fig.…”
Section: Significancesupporting
confidence: 52%
“…2 C and D) all decreased affinity by at least fivefold. This segment of UL50 and M50, particularly E56 and Y57, and the corresponding segment of their pseudorabies virus and Kaposi's sarcoma herpes virus homologs have previously been shown to be important for interaction with the other NEC subunit in less quantitative coimmunoprecipitation and colocalization assays (16,19,32,33). We also found that several substitutions that alter residues between positions 121 and 129 of M50 and 125 and 139 of UL50 (at the top of the groove and within the cavity in Fig.…”
Section: Significancesupporting
confidence: 52%
“…However, the spatiotemporal regulation of NEC formation and function and how nucleocapsids are recruited into these vesicles remain incompletely understood. Mutational studies of pUL34 have already shed some light on the mechanism of NEC formation and function (12,(18)(19)(20)(21)(22)(23), but corresponding data on pUL31 homologs are less comprehensive.…”
Section: Discussionmentioning
confidence: 99%
“…For complementation studies, cell lines stably expressing the pUL31-NLS and pUL31-NES mutant constructs were generated. To this end, RK13 cells were transfected with the mutated pcDNA-UL31 plasmids by calcium phosphate precipitation (19,33). Cells were selected in medium containing 0.5 mg/ml G418, and correct protein expression was verified by indirect immunofluorescence and Western blot analysis.…”
Section: Cells and Virusesmentioning
confidence: 99%
See 1 more Smart Citation
“…To introduce mutations into the gH sequence, a QuikChange II XL site-directed mutagenesis kit (Agilent Technologies) was used as described recently (28). Specific primers (Table 1) derived from the genomic sequence of PrV-Ka (GenBank accession no.…”
Section: Cells and Virusesmentioning
confidence: 99%